A fractal kinetics SI model can explain the dynamics of COVID-19 epidemics - Kosmidis, Kosmas; Macheras, Panos (PLOS ONE, 2020)
The COVID-19 pandemic has already had a shocking impact on the lives of everybody on the planet. Here, we present a modification of the classical SI model, the Fractal Kinetics SI model which is in excellent agreement with the disease outbreak data available from the World Health Organization. The fractal kinetic approach that we propose here originates from chemical kinetics and has successfully been used in the past to describe reaction dynamics when imperfect mixing and segregation of the reactants is important and affects the dynamics of the reaction. The model introduces a novel epidemiological parameter, the ``fractal{''} exponenthwhich is introduced in order to account for the self-organization of the societies against the pandemic through social distancing, lockdowns and flight restrictions.